Dbx1 controls the development of astrocytes of the intermediate spinal cord by modulating Notch signaling - Sartoretti, María Micaela (2022)
Significant progress has been made in elucidating the basic principles that govern neuronal specification in the developing central nervous system. In contrast, much less is known about the origin of astrocytic diversity. Here we demonstrate that a restricted pool of progenitors in the mouse spinal cord, expressing the transcription factor Dbx1, produces a subset of astrocytes, in addition to interneurons. Ventral p0-derived astrocytes (vA0) exclusively populate intermediate regions of spinal cord with extraordinary precision. Postnatal vA0 population comprises gray matter protoplasmic and white matter fibrous astrocytes and a group of cells with strict radial morphology contacting the pia. We identified that vA0 cells in the lateral funiculus are distinguished by the expression of Reelin and Kcnmb4. We show that Dbx1 mutants have increased vA0 cells at the expense of p0-derived interneurons. Manipulation of the Notch pathway, together with the alteration in their ligands seen in Dbx1 knock-outs, suggest that Dbx1 controls neuron-glial balance by modulating Notch-dependent cell interactions. In summary, this study highlights that restricted progenitors in dorsal-ventral neural tube produce region-specific astrocytic subgroups and that progenitor transcriptional programs highly influence glial fate and are instrumental in creating astrocyte diversity.